2019
DOI: 10.1080/21645515.2019.1663121
|View full text |Cite
|
Sign up to set email alerts
|

Varicella vaccine dose depended effectiveness and waning among preschool children in Hong Kong

Abstract: In Hong Kong, universal varicella vaccination was introduced in July 2014 with a two-dose schedule but the vaccines had been available in the private market since 1996. With data from varicella notification and surveys on immunization coverage, we used the screening method to estimate dose-specific varicella vaccine effectiveness (VE) among preschool children in Hong Kong before universal vaccination. We estimated the VE of one-and two-dose varicella vaccination against all notified varicella as 69.4% (95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In addition, this study revealed that the shorter the two doses intervals, the better the effect of the vaccine, suggesting that different national or regional recommendations relating to this interval will result in different VE of the 2-dose vaccine. These findings are consistent with the previous study showing the shortening of the interval between the first dose and the second dose of vaccination should reduce breakthrough varicella and outbreaks in preschool (39) was no significant difference in VE of the 2-doses vaccine in all investigated time intervals >27 days up to >3 years between varicella doses (32). This may be due to the protection induced by one dose vaccine of varicella did not decrease in their study, but our study and other study revealed the reduced long-term VE of one-dose vaccination and the reduction in efficacy over time (13,14,40).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, this study revealed that the shorter the two doses intervals, the better the effect of the vaccine, suggesting that different national or regional recommendations relating to this interval will result in different VE of the 2-dose vaccine. These findings are consistent with the previous study showing the shortening of the interval between the first dose and the second dose of vaccination should reduce breakthrough varicella and outbreaks in preschool (39) was no significant difference in VE of the 2-doses vaccine in all investigated time intervals >27 days up to >3 years between varicella doses (32). This may be due to the protection induced by one dose vaccine of varicella did not decrease in their study, but our study and other study revealed the reduced long-term VE of one-dose vaccination and the reduction in efficacy over time (13,14,40).…”
Section: Discussionsupporting
confidence: 93%
“…29 Concerns about vaccine failure due to waning immunity were suggested by previous studies of specific vaccine types or population cohorts. 30 31 32 33 In this study, considering the mean age of varicella was older in the vaccinated population, the waning immunity may be the result from secondary vaccine failure. 34 35 Moreover, the reason for the possibility of the waning immunity could originate from not only population outbreaks but also from the vaccine itself.…”
Section: Discussionmentioning
confidence: 93%
“…We also found higher VE of second-dose vaccination, which was in line with reports from the U.S., Europe, and Asia. 33 38 39 40 41 Earlier studies showed a decline in incidence with the introduction of a two-dose program 40 42 or a decreased occurrence of outbreaks, 16 43 but the actual effectiveness compared to the single-dose vaccine group was rarely studied. In this study, the effectiveness of secondary vaccination was estimated with consistency, enabling comparison with the primary-only vaccinated group.…”
Section: Discussionmentioning
confidence: 99%
“…In Hong Kong, the effectiveness of a one-dose vaccine was 69.4%. It increased to 93.4% when the primary dose was given at 12 months and then a second dose was given at around 6 years old [ 36 ]. However, they mentioned that the two-dose regimen with a short interval should be considered to reduce varicella outbreaks.…”
Section: Discussionmentioning
confidence: 99%